Keanekaragaman Vegetasi Hutan Mangrove Sebagai Bahan Pengayaan Mata Kuliah Ekologi Lahan Basah - Hardiansyah Hardiansyah; Noorhidayati Noorhidayati; Mahrudin Mahrudin (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2019)
One of the habitats in the wetlands is the Ecosystem of Mangrove which has a diversity of flora and fauna. This study aims to describe the diversity of vegetation in the mangrove forest area of Sungai Rasau Village, Tanah Laut Regency and obtain valid and practical handout teaching materials. The research method used is descriptive method and development research. The main subjects of this study were 2 experts and 5 students as test subjects. Data were analyzed descriptively. The results showed that the tree vegetation of Sonneratia alba, Hibiscus tiliaceus, Heritiera littoralis, Avicennia marina, Excoecaria agallocha, Rhizopora apiculata, Rhizopora mucronata, Nypa fruticans, Sonneratia caseolaris with a diversity index of 1,848 (medium). Shrubs and herbs, Derris trifociata Acanthus ilicifolius L, Pluchea indica L, Galinsoga parviflora, Cyperus kyllinga, and Fimbristylis dichotoma have moderate diversity index (H'=1.662). The handout developed "Diversity of Mangrove Vegetation in Sungai Rasau Village, Tanah Laut Regency" as Enrichment Material for Wetland Ecology Courses has very valid criteria with very good legibility tests.